2020
DOI: 10.3390/ijms21082688
|View full text |Cite
|
Sign up to set email alerts
|

3D Culture of MSCs on a Gelatin Microsphere in a Dynamic Culture System Enhances Chondrogenesis

Abstract: Recent advancement in cartilage tissue engineering has explored the potential of 3D culture to mimic the in vivo environment of human cartilaginous tissue. Three-dimensional culture using microspheres was described to play a role in driving the differentiation of mesenchymal stem cells to chondrocyte lineage. However, factors such as mechanical agitation on cell chondrogenesis during culture on the microspheres has yet to be elucidated. In this study, we compared the 2D and 3D culture of bone-marrow-derived me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
0
31
0
1
Order By: Relevance
“…The unloaded GMs alone might not induce chondrogenesis without conditions that mimic the native cartilage environment. The manipulation of the culture environment that closely resembles the in vivo condition, such as by mechanical stimulation, might be able to drive cellular differentiation, as demonstrated by our recent work [ 66 ].…”
Section: Gelatin Microsphere Effect On Chondrocyte Behaviormentioning
confidence: 96%
See 1 more Smart Citation
“…The unloaded GMs alone might not induce chondrogenesis without conditions that mimic the native cartilage environment. The manipulation of the culture environment that closely resembles the in vivo condition, such as by mechanical stimulation, might be able to drive cellular differentiation, as demonstrated by our recent work [ 66 ].…”
Section: Gelatin Microsphere Effect On Chondrocyte Behaviormentioning
confidence: 96%
“…GMs alone increase the synthesis of sulfated glycosaminoglycan (sGAG), a marker of chondrogenesis, by adipose stem cells [ 34 , 35 ]. A recent study also indicated that GMs support chondrogenesis, as portrayed by the increased staining of the chondrogenic lineage differentiation of bone-marrow MSCs cultured on GMs [ 66 ]. It was speculated that the chondrogenic effect of GMs is attributable to the presence of amino acid sequences (arginine–glycine–aspartic acid (RGD) sequence) in gelatin protein [ 67 ].…”
Section: Gelatin Microsphere Effect On Chondrocyte Behaviormentioning
confidence: 99%
“…In addition, recent studies of cartilage tissue engineering have investigated the effect of 3D culture on MSC chondrogenic differentiation, which represents a potential way to mimic the in vivo cartilage tissue environment. Synthetic and natural materials, such as 3D-printed bioreactor chambers, hydrogels, and microspheres, have been developed as tools to create a 3D microenvironment for MSCs [ 58 61 ]. For example, Sulaiman et al compared the 2D and 3D cultures of hBMSCs and found that 3D culture of BMSCs on gelatin microspheres enhanced their stemness and chondrogenic differentiation compared to 2D culture on a standard tissue culture plate [ 61 ].…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Bone marrow-derived mesenchymal stem cells (BMSCs) have the potential for chondrogenic differentiation, self-renewal, and proliferation with less loss of phenotype than chondrocytes, and have been considered as an ideal cell source for tissue-engineered cartilage formation 4 . Previous studies have showed that BMSCs can be induced into hyaline-like cartilage tissue with high expression of aggrecan(ACAN), collagen type ( COL2), and SOX9 in high-density pellets or scaffold in vitro culture 5,6 . However, the extremely low percentage of BMSCs in the bone marrow means that in vitro expansion is the rst step to obtain enough cell numbers before chondrogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the suitable medium containing growth factors is also an essential factor for tissue engineering. So far, the most widely applied media to date are almost commercially synthesized reagents, which have shown excellent chondrogenic-differentiation capacity in tissue-engineered cartilage formation [6][7][8] . While these media contain kinds of ectogenic growth factors and cost expensive, whether some autologous biomaterials with similar induction effects can be an alternative to the synthetic reagents, it is still worthy of further study.…”
Section: Introductionmentioning
confidence: 99%